# Re-arranging formulae

#### Monkeyseat

##### Full Member

(^ Make sure you can see pictures ^)

I do this:

Square both sides:

A^2=3P

Divide by 3:

(A^2)/3 = P

P = (A^2)/3

Yet the answers say it is meant to be:

P=3A^2

Where am I going wrong?

Cheers.

#### morson

##### Full Member
Your solution is $$\displaystyle P = \frac{A^2}{3}\$$

Let's substitute our solution into the equation to check:

$$\displaystyle A = \sqrt{3 \frac{A^2}{3}\ }\ = \sqrt{A^2}\$$

This is only true for non-negative A.

So, let's revise the solution:

$$\displaystyle P = \frac{A^2}{3}\$$, for non-negative A.

#### Monkeyseat

##### Full Member
Sorry, so which solution was correct? Is the answer from the book incorrect?

Thanks.

#### morson

##### Full Member
The book's answer is not correct in the general case, no.

#### Monkeyseat

##### Full Member
Oh right, thanks.

It wasn't really a book, it was the mark scheme for a GCSE test so I didn't think it would be wrong but I couldn't find how they got that answer...

Thanks for the help.